Building a Culture of Peace through Peace Education as the Foundation for Merdeka Campus Transformation - Irawan, Hendri; Tutik Wijayanti; Satrio Alpen Pradanna; Anif Istianah (Forum Ilmu Sosial, 2024)
Higher education is a crucial foundation for shaping individuals who are both high-quality and positively contribute to society.This study reviews the transformation of peace education within the Merdeka Campus environment, an innovative approach in Indonesia's higher education system. The "Freedom to Learn" concept emphasizes students' autonomy in managing their learning processes according to their interests and potential. This approach not only strengthens academic aspects but also instills values of peace and cooperation among students within the campus environment. By fostering creativity and open dialogue, the Merdeka Campus creates an atmosphere conducive to shaping future leaders committed to peace. The study employs a literature review method, providing a foundation for the implementation of the Merdeka Belajar concept in the context of peace education. It outlines strategies for curriculum development that support a deeper understanding of conflict resolution and peaceful solutions. Additionally, the study highlights the role of lecturers as facilitators in guiding students towards a holistic understanding of the concept of peace. The findings indicate that the Merdeka Belajar approach to peace education within the Merdeka Campus environment positively impacts student development, both in terms of knowledge and attitudes